Local Drivers of Marine Heatwaves: A Global Analysis With an Earth System Model - Vogt, Linus; Burger, Friedrich A.; Griffies, Stephen M.; Frölicher, Thomas L. (Frontiers in Climate, 2022)
Marine heatwaves (MHWs) are periods of extreme warm ocean temperatures that can have devastating impacts on marine organisms and socio-economic systems. Despite recent advances in understanding the underlying processes of individual events, a global view of the local oceanic and atmospheric drivers of MHWs is currently missing. Here, we use daily-mean output of temperature tendency terms from a comprehensive fully coupled coarse-resolution Earth system model to quantify the main local processes leading to the onset and decline of surface MHWs in different seasons. The onset of MHWs in the subtropics and mid-to-high latitudes is primarily driven by net ocean heat uptake associated with a reduction of latent heat loss in all seasons, increased shortwave heat absorption in summer and reduced sensible heat loss in winter, dampened by reduced vertical mixing from the nonlocal portion of the K-Profile Parameterization boundary layer scheme (KPP) especially in summer. In the tropics, ocean heat uptake is reduced and lowered vertical local mixing and diffusion cause the warming. In the subsequent decline phase, increased ocean heat loss to the atmosphere due to enhanced latent heat loss in all seasons together with enhanced vertical local mixing and diffusion in the high latitudes during summer dominate the temperature decrease globally. The processes leading to the onset and decline of MHWs are similar for short and long MHWs, but there are differences in the drivers between summer and winter. Different types of MHWs with distinct driver combinations are identified within the large variability among events. Our analysis contributes to a better understanding of MHW drivers and processes and may therefore help to improve the prediction of high-impact marine heatwaves.